Penyusunan Perangkat Pembelajaran Berbasis Pendidikan Karakter bagi Guru Madrasah Aliyah Se-Kota Semarang - Indiati, Intan; Shodiqin, Ali; Nuvitalia, Duwi; Rahmawati, Noviana Dini; Muhtarom, Muhtarom (Perkumpulan Kualitama Edukatika Indonesia, 2023)
The aim of this service is to equip Madrasah Aliyah teachers to create learning tools that integrate character education in learning activities. The method used to achieve this goal is with training with more demonstrations, questions and answers and practice as well as mentoring. The training material is presented with more practice than theory, with a ratio of 30% theory and 70% practice. The results of this service produce national character-based learning implementation plan (RPP) products and national character-based learning evaluation instruments. The national character-based RPP in the indicator component explicitly emphasizes the character that must be displayed or is to be achieved. In general, the learning objectives component only writes down learning outcomes in the cognitive domain. Meanwhile, the component of learning objectives based on national character is clearly exposed to the conditions given to students to be able to display character both in the learning and assessment processes. Meanwhile, in this evaluation instrument, the affective aspects of learning can be observed and measured well. In this evaluation instrument the focus is on the character that will be achieved, with assessment criteria A for doing well, assessment B for doing and needs improvement and assessment C for not doing, from these criteria the teacher can measure the level of student character development that has not been observed so far is well.